2014
DOI: 10.1123/jab.2013-0133
|View full text |Cite
|
Sign up to set email alerts
|

Intraindividual Movement Variability Within the 5 m Water Polo Shot

Abstract: The purpose of this study was to explore movement variability of throwing arm and ball release parameters during the water polo shot and to compare variability between successful (hit) and unsuccessful (miss) outcomes. Seven injury free, subelite, females completed 10 trials of the 5 m water polo penalty shot. Intraindividual coefficient of variation percentage (CV%) values were calculated for elbow and wrist angular displacement, wrist linear velocity and ball release parameters (height, angle and velocity). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…5,37 Superior throwing performance has been shown to be characterised by decreased movement variability at critical points within the penalty shot. 54 Although shooting proficiency is adversely affected by increased exertion, height out of the water, elbow angle and position at release, ball speed and accuracy were all maintained under fatigue. 55 Reduction in movement variability at the elbow before ball release suggests that a threshold may exist to improve throwing accuracy and potentially reduce injury risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,37 Superior throwing performance has been shown to be characterised by decreased movement variability at critical points within the penalty shot. 54 Although shooting proficiency is adversely affected by increased exertion, height out of the water, elbow angle and position at release, ball speed and accuracy were all maintained under fatigue. 55 Reduction in movement variability at the elbow before ball release suggests that a threshold may exist to improve throwing accuracy and potentially reduce injury risk.…”
Section: Discussionmentioning
confidence: 99%
“…To improve athletes throwing proficiency, the literature demonstrates value in coaches focussing on increasing athletes overall fitness 55 as well as practicing throwing skill under pre-fatigue conditions. 54 Dynamic shoulder stability is derived from muscular as well as neuromuscular control. Recent research has shown that the quality of an individual's proprioception is associated with the level at which they perform in their sport.…”
Section: Discussionmentioning
confidence: 99%
“…Although highly dynamic movements can produce errors in marker tracking due to the movement of the skin and muscle (Gordon & Dapena, 2006), triad clusters of markers have been shown to produce more accurate results (Elliott et al, 2007) and reduce the effect of soft tissue artefacts (Cappozzo et al, 1995). The same upper-limb model has been used previously to evaluate shoulder and humerus rotations in volleyball (Seminati et al, 2015), overarm throwing technique (Taylor et al, 2015), water polo shot technique (Taylor et al, 2014) and hand-cyclist kinematics (Abel et al, 2010). Validation and additional information on the model can be found in Cutti et al (2005) and Murray (1999).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The use of the CV to assess motor coordination variability is common. 1,9,28,33 The average of the angular velocity peaks was also used as a descriptive parameter for the data. Prior to the calculation of means and CVs, outliers were removed with a conservative filter based on the median and the Median Absolute Deviation (MAD).…”
Section: Discussionmentioning
confidence: 99%